1995
DOI: 10.1136/vr.136.12.292
|View full text |Cite
|
Sign up to set email alerts
|

Euthanasia of day-old chicks with carbon dioxide and argon

Abstract: The efficacy for the euthanasia of day-old chicks of mixtures of carbon dioxide and air, or carbon dioxide and argon containing 1, 2 or 5 per cent residual oxygen, or argon containing 1 or 2 per cent residual oxygen was tested in three experiments. The time to the onset of unconsciousness of individual chicks, determined from the time to loss of posture, was similar during their exposure to 2 per cent oxygen in argon, 20, 30 or 40 per cent carbon dioxide in argon with 2 per cent residual oxygen, or 90 per cent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 0 publications
0
12
0
Order By: Relevance
“…Continued exposure to the gas leads to hypercapnic hypoxia, respiratory depression, and ultimately death [ 8 ]. Raj and Whittington [ 9 ] studied the efficacy of either a 90% CO 2 treatment or mixture of 20, 30, 40% CO 2 in argon. Their study [ 9 ] reported that day-old chicks subjected to 90% CO 2 in the air died within two minutes of exposure.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Continued exposure to the gas leads to hypercapnic hypoxia, respiratory depression, and ultimately death [ 8 ]. Raj and Whittington [ 9 ] studied the efficacy of either a 90% CO 2 treatment or mixture of 20, 30, 40% CO 2 in argon. Their study [ 9 ] reported that day-old chicks subjected to 90% CO 2 in the air died within two minutes of exposure.…”
Section: Introductionmentioning
confidence: 99%
“…Raj and Whittington [ 9 ] studied the efficacy of either a 90% CO 2 treatment or mixture of 20, 30, 40% CO 2 in argon. Their study [ 9 ] reported that day-old chicks subjected to 90% CO 2 in the air died within two minutes of exposure. European Union guidelines of Council Directive 93/119/EC on animal protection at the time of slaughter or killing, requires chicks to be exposed to the highest possible concentration of CO 2 dispensed from a 100% source and requires that the gas concentration be maintained until the death of the chicks [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Raj (1996) found that either 90% argon in air or a mixture of 30% carbon dioxide and 60% argon in air is preferable to a high concentration of carbon dioxide for stunning and killing of turkeys. Raj and Whittington (1995) reported that chickens could also be killed in argon without inducing any apparent respiratory discomfort before the loss of consciousness, although behavioural signs of agitation were obvious. We have previously developed a mixture of carbon dioxide and oxygen for the induction of an acceptable euthanasia in rats (Coenen et al, 1995).…”
Section: Introductionmentioning
confidence: 99%